Comparison of Interleukin-1β Levels In Open and Closed Fracture Patients of The Long Bone In Padang - Iqbal Arnif; Roni Eka Sahputra; Hendra Maska (HM Publisher, 2021)
Background and Purpose. Trauma is a significant burden on causes of death, disability, and financing in least developed or